2004
DOI: 10.1007/s10346-003-0004-y
|View full text |Cite
|
Sign up to set email alerts
|

Undrained dynamic-loading ring-shear apparatus and its application to landslide dynamics

Abstract: Landslides are gravitational mass movements of rock, debris or earth. Some move very slowly, thus conforming to the field of statics, but some move rapidly. Study of the initiation and motion of rapid landslides needs to develop "Landslide Dynamics" involving dynamic loading and dynamic generation/dissipation of excess pore-water pressure. New developments in science can be facilitated by new technological advances. This study aimed to develop a new apparatus that can geotechnically simulate the formation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 258 publications
(140 citation statements)
references
References 13 publications
5
134
0
1
Order By: Relevance
“…As a result, the shear resistance may drastically decrease, leading to slope instability. Sassa et al (2004) noted that the process of grain crashing that occurs in weathered pumice and tuŠ during strong shaking may be an additional factor that would determine the high velocity and long run-out distance of the landslides.…”
Section: Discussion On the Causes Of Catastrophic Landslidesmentioning
confidence: 99%
“…As a result, the shear resistance may drastically decrease, leading to slope instability. Sassa et al (2004) noted that the process of grain crashing that occurs in weathered pumice and tuŠ during strong shaking may be an additional factor that would determine the high velocity and long run-out distance of the landslides.…”
Section: Discussion On the Causes Of Catastrophic Landslidesmentioning
confidence: 99%
“…Because of such rapid dynamic loading, the saturated slope failed under undrained conditions. With reference to dynamic-loading ring-shear tests on saturated volcanoclastic deposits, Sassa et al (2004) demonstrated that only a slight additional shear stress was required to cause failure under undrained conditions. Owing to the difficulty in quantifying all the variable requirements in this case-history, soil stability back-analyses should lead to a better prediction of the required dynamic load for slope failure.…”
Section: Discussionmentioning
confidence: 99%
“…Liquefaction takes place in soils with loose meta-stable structure so long as grain crushing and the resulting volume reduction takes place under the given overburden pressure. Sassa et al (2004) described a dynamic-loading ring-shear apparatus that can simulate the formation of shear zones including long and rapid shear displacements that occur in highvelocity or earthquake-induced landslides, under undrained loading conditions. Iverson et al (1997) indicated that most landslides that mobilize to form debris flows are triggered by increased pore-water pressures associated with rainfall, snowmelt, or groundwater inflow from adjacent areas.…”
Section: Introductionmentioning
confidence: 99%
“…The continuously varying shear area leads to inconstant and heterogeneous normal stress in soil (Dai et al 1998). The ring shear method, therefore, is adopted to measure the shear strength of sliding zone soil as a large shear displacement is allowed while the shear area and the normal stress can be maintained constant during the test (American Society for Testing and Materials 1964; Sassa et al 2004;Yang et al 2001). To estimate the residual shear strength of the landslide slip surface.…”
Section: Methodsmentioning
confidence: 99%
“…In the last decade, the role that sliding zone soil, as well as its liquefaction, plays in the development and occurrence of large landslides have been increasingly stressed (Wang et al 2002(Wang et al , 2007Hu et al 2009;Sassa et al 2004;Zhang et al 2011a;Rozos et al 2011Rozos et al , 2013Mohamed et al 2013). More importantly, similarly to that observed by Hu et al (2009) during ring shear tests on soil of the Yigong long-distance landslide, obvious liquefaction of shear strips are observed in the sample S01.…”
Section: Liquefaction Of the Sliding Zone Soilmentioning
confidence: 99%